Domestic evolution. - Priest, Isabelle (RIBA Journal, 2024)
This article discusses the design and construction of architect Will Burges' self-built family home, Six Columns, in Crystal Palace, London. Burges emphasizes that the house is not a finished product, but rather a work in progress that can be adapted and fine-tuned over time. The design takes inspiration from its suburban surroundings and incorporates various architectural references, such as Mies van der Rohe's Barcelona Pavilion. The article also mentions the sustainable features of the house, including its low carbon footprint. Overall, Six Columns is a unique and personalized home that reflects Burges' architectural vision.